2016
DOI: 10.1186/s12863-016-0421-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and detection of chromosomal regions affecting the major milk proteins and their post translational modifications in Danish Holstein and Danish Jersey cattle

Abstract: BackgroundIn the Western world bovine milk products are an important protein source in human diet. The major proteins in bovine milk are the four caseins (CN), αS1-, αS2-, β-, and k-CN and the two whey proteins, β-LG and α-LA. It has been shown that both the amount of specific CN and their isoforms including post-translational modifications (PTM) influence technological properties of milk. Therefore, the aim of this study was to 1) estimate genetic parameters for individual proteins in Danish Holstein (DH) (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 43 publications
7
65
8
Order By: Relevance
“…We did not detect a QTL signal on BTA25 where the FAM20C gene is located [between 43.86 to 43.90 Mbp (BTAU 4.0)], neither for individual α S2 -CN phosphorylation isoforms nor for α S1 -and α S2 -CN PD. This is in line with results reported by Bijl et al (2014) and Buitenhuis et al (2016) and suggests that no FAM20C variants are segregating in the Dutch Holstein population or in the Danish Holstein and Danish Jersey populations. Regions associated with multiple traits were found on BTA1, 6, 11, and 14, and their effects will be discussed in detail.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We did not detect a QTL signal on BTA25 where the FAM20C gene is located [between 43.86 to 43.90 Mbp (BTAU 4.0)], neither for individual α S2 -CN phosphorylation isoforms nor for α S1 -and α S2 -CN PD. This is in line with results reported by Bijl et al (2014) and Buitenhuis et al (2016) and suggests that no FAM20C variants are segregating in the Dutch Holstein population or in the Danish Holstein and Danish Jersey populations. Regions associated with multiple traits were found on BTA1, 6, 11, and 14, and their effects will be discussed in detail.…”
Section: Resultssupporting
confidence: 92%
“…This resulted in lower degrees of phosphorylation of α S1 -and α S2 -CN, as shown by the negative association of the BB genotype with both α S1 -and α S2 -CN PD. Buitenhuis et al (2016) and Fang et al (2017) did not detect significant effects of β-LG genotypes on individual α S2 -CN phosphorylation isoforms, α S1 -CN PD and α S2 -CN PD, in Danish Holstein and Danish Jersey or French Montbéliarde. Differences between studies might be due to the genetic differences between studied breeds (Holstein, Montbéliarde, and Jersey), such as differences in linkage disequilibrium between β-LG genotypes and other variants that affect the traits of interest, limited sample size of Buitenhuis et al (2016) and Fang et al (2017), and the use of different analytical methods.…”
Section: Bta11mentioning
confidence: 65%
“…There were eleven sites shared between Holstein and Nordic Red Cattle, two sites between Holstein and Jersey, and one site between Nordic Red Cattle and Jersey. Among these sites were gene variants, such as ABCA12 (Chr2:103,682,772-103,684,297 in Holstein & Jersey) associated with growth and development, 55 , 56 TTC1 (Chr7:73,725,513-73,725,918 in Holstein & Nordic Red Cattle) with cold tolerance, 57 VWA3B (Chr11:3,521,329-3,522,551 in Holstein & Nordic Red Cattle) with milk glycosylated kappa-casein percentage, 58 and were intergenic variants, such as Chr15:41,393,393-41,393,780 (in Jersey and Nordic Red Cattle) and Chr20:26,812,159-26,812,834 (in Holstein and Jersey) overlap QTL associated with calving traits, 59 , 60 Chr20:45,816,245-45,820,519 (in Holstein & Nordic Red Cattle) with meat and carcass trait, 61 and Chr23:49,778,653-49,782,567 (in Holstein and Nordic Red Cattle) with body weight 62 . We also identified a highly differentiated fertility associated gene DST/BPAG1 63 , 64 (Chr23:3,486,232-3,486,603) in Nordic Red Cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, one selective sweep study in a German Holstein population revealed an extended range of LD in haplotypes that contain the casein cluster [53]. Secondly, GWA study on casein traits in a Danish Holstein population identified a broad GWAS peak (BTA6:60-100 Mb) that contains the casein cluster [54]. The broad GWAS peak also indicate high LD in this regions, that matched with the findings from Qanbari et al [53] Another explanation for the high MAF of CNVR 547 might be the direct selection on the variant itself.…”
Section: Interesting Cnvrmentioning
confidence: 99%